The power of the mindbody: Collective somatic learning in community organizing groups - Jessica Roadman (Adult Education Research Conference, 2021)
Embodiment theory posits that learning is not limited to the cognitive functions of the brain, but is the adaptation resulting from multi-system responses to inputs. Somatics offers techniques for increased awareness of response mechanisms, which allows for more controlled self-regulation. This paper explores the benefits of engaging in somatic practicing as a tool for individual grounding catalysed for change in the context of the organizing group the Powerful Moms Who Care. It focuses on the emergence of connected activism through trauma processing, gaining body autonomy, and unconstrained visioning of the future as a result of integrating somatic practices.
Keywords: Embodiment; somatics; community organizing; grassroots